2009
DOI: 10.1117/12.826807
|View full text |Cite
|
Sign up to set email alerts
|

Next generation x-ray sensor (XRS) for the NOAA GOES-R satellite series

Abstract: The X-Ray Sensor (XRS) has been making observations of the solar soft X-ray irradiance for over thirty years onboard National Oceanic and Atmospheric Administration's (NOAA) Geostationary Operational Environmental Satellites (GOES). The XRS provides critical information about the solar activity for space weather operations, and the standard X-ray classification of the solar flares is based on its measurements. The GOES-R series of XRSs, with the first in the series to launch in 2014, has a completely new instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 8 publications
0
38
0
Order By: Relevance
“…The geolocated RBN data presented in Figures 3a-3d are available as Data Set S1 in the supporting information. Figure 3e shows GOES 15 X-ray sensor [Chamberlin et al, 2009] …”
Section: Case Study: Ionospheric Impacts Of the 13 May 2013 Solar Flarementioning
confidence: 99%
“…The geolocated RBN data presented in Figures 3a-3d are available as Data Set S1 in the supporting information. Figure 3e shows GOES 15 X-ray sensor [Chamberlin et al, 2009] …”
Section: Case Study: Ionospheric Impacts Of the 13 May 2013 Solar Flarementioning
confidence: 99%
“…" We analyze an example of the flare trigger data on 2013 December 31 (SOL2013-12-31). The GOES (Chamberlin et al 2009) and FERMI (Atwood et al 2009) light curves are shown in Figure 1, where the vertical dashed line highlights the time when the mode switched from flare search study (the EIS 266″ slot data) to flare study (EIS raster data). We checked all the GBO detectors for evidence of saturation, and the data plotted in Figure 1 are from a detector that did not appear to show significant evidence of saturation.…”
Section: Discussionmentioning
confidence: 99%
“…(Evans et al, 2010) using instruments similar in design to the SOHO/SEM. A next generation of EUVS and XRS for the GOES-R+ program with expanded capabilities is preparing for launch in 2016 Chamberlin et al, 2009). The instrument EUVS optics consists of concave reflection gratings, thin freestanding foil filters, and arrays of silicon diodes.…”
Section: Timed/seementioning
confidence: 99%